SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN DOSEN BERPRESTASI DENGAN MENGGUNAKAN METODE WP(WEIGHTED PRODUCT) DI UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAKARTA - Rizqi Tri Atmojo (2020)
In general, the understanding of lecturers is a professional lecturer in charge of teaching, educating, directing, along with giving guidance, evaluation, training and assessment of students. Meanwhile, the law was reduced to law No. 14 Th. 2005 discussing the lecturer, lecturer is a professional scientist and lecturer whose main task is to spread and inflate knowledge through research, serve to society and education. National Development University Veteran Jakarta is a PTN in the environment of the Ministry of Education and Culture which is located in South Jakarta, DKI Jakarta with its campus position in the city of Depok and Bogor Regency, West Java. In order to motivate the quality improvement of lecturers, the university leadership conducted an accomplished lecturer election, in choosing an accomplished lecturer by the Organizing Committee of outstanding lecturers at the National Development University Veteran Jakarta is not yet supported by good system tools, such as decision support system. Therefore, authors build a SPK (decision support system) that can support decision making in choosing an accomplished lecturer using certain data to serve it through Weighted Product (WP) method with basic concept can find the value of weight from performance rating in each attribute alternative. From the decision support system successfully resulted in the form of a list of achievement lecturers achievers. At the Jakarta National Development University.